A MANIFESTO FOR PHILOSOPHY. Issue 59 (2021) - Buxton, Rebecca; Whiting, Lisa
Abstract : Most academics in philosophy departments accept that the discipline needs to change for the better. In this piece, Rebecca Buxton and Lisa Whiting offer several proposals for how to make philosophy a more inclusive place for everyone.